Photoperformance as Dramaturgy of Light and Symptom-Image: A Sensitive Scenography of Mourning and Memory (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This article presents a critical and performative study on the power of photo-performance as an artistic language capable of staging grief, pain, and individual and collective memory. Based on the series of works entitled Absences, produced between 2020 and 2024, it discusses how the photographic image can operate as a symptom, as a suspended gesture, and as emotional scenography. The artist's body is central to this process – enunciating experiences of personal loss, creating tension in spaces of urban and religious memory, and reconfiguring icons of art history. Drawing on the concepts of image-symptom (DIDI-HUBERMAN, 2013), gesture (AGAMBEN, 2000), photographic theatricality (DIÉGUEZ, 2020), and site-specificity (FOSTER, 2014; KWON, 2002), the article proposes performative photography as a dramaturgy of light and space. Analysis of the works reveals how common objects – blankets, fabrics, bones – become symbolic operators, establishing a dramaturgy of intimacy and social critique.